Bowel Injury in Blunt Abdominal Trauma - Role of Serial Focused Assessment Sonography for Trauma (FAST) Scan - Atif Sharif, Tasleem Akhtar, Naeem Zia (Journal of Rawalpindi Medical College, 2015)
Background: To analyse the role of Serial FAST scan in diagnosing bowel injury in blunt abdominal trauma Methods: In this descriptive study FAST scan was performed as part of the primary or secondary survey of the trauma patient in the emergency department, in all patients with suspected blunt abdominal trauma. Follow up scans were performed depending on the clinical condition. The findings were then confirmed with either a computed tomography (CT) or emergency exploration. The validity of FAST scan and Serial FAST scans in comparison to CT/ELAP was documented. Special attention was paid for diagnosing bowel injury. Initial FAST negative were conducted to Serial FAST scans and increased fluid and development of peritonitis lead to exploration. Results: This study included 174 patients with suspected blunt abdominal trauma. The mean age was 27.40±15.30 years with 93.6% males. Road traffic accidents accounted for 58.6% cases.There were 108 patients who underwent exploration. Majority (53) had isolated hollow viscus injury. Haemodynamically unstable patients had significantly more positive FAST scans and more positive CT/ELAP (p <0.05). Serial FAST scans increased the sensitivity and specificity of FAST from 70.83% to 98.67% and 80.36% to 93.10% and 100% diagnostic accuracy for bowel injury. Conclusion: Serial FAST scan is a good diagnostic modality with accuracy comparable to CT for clinically significant exploratory laparotomies, thus a good predictor for exploration when suspecting bowel injury.